KOMPARASI FENOMENOLOGI EDMUND HUSSERL DAN MARTIN HEIDEGGER - Fitrah, Muhammad; Indah, Astrid Veranita (Sulesana: Jurnal Wawasan Keislaman, 2024)
Phenomenology has developed since the 15th century. Many philosophers rejected Church doctrines and carried out a reform movement known as the enlightenment period. Phenomenology was developed by Edmund Husserl in the 20th century, who became known as the father of phenomenology. Rather than being a science, phenomenology initially emerged as a research method developed by Edmund Husserl as part of the study of philosophy and sociology. As a scientific method, phenomenology is a way of formulating science through certain stages. Phenomenology as a research method is seen as the study of phenomena, the study of nature and meaning. This research focuses on the way we perceive reality that appears through experience or consciousness. Husserl's phenomenology is a speculative attempt to determine nature which is entirely based on examining and analyzing what appears or returns to the objects themselves. Meanwhile, Heidegger's phenomenology is based on the relationship between language, interpretation, and objective nature.